ASSOCIATION BETWEEN AGES AND GLUCOCORTICOID-INDUCED DIABETES MELLITUS INCIDENCE IN INTRACRANIAL TUMOR PATIENTS - Mariska, Irina Kemala Nasution & Aida Fithrie (International Journal of Research Science and Management, 2020)
Background: glucocorticoids are the main therapy for treating peritumoral edema in patients with intracranial tumors. The use of glucocorticoids has side effects, one of which is hyperglycemia or what is called Glucocorticoid-Induced Diabetes Mellitus (GIDM). Hyperglycemia in brain tumor patients is associated with decreased survival, increased recurrence and degeneration to malignancy. Objective: to determine the association between age and the incidence of GIDM in intracranial tumor patients. Method: this study uses a cohort design. Sampling was conducted at Ruang Rawat Inap Terpadu (Rindu) H. Adam Malik General Hospital Medan. Samples were taken as many as 30 subjects consecutively. Blood sugar levels were checked twice a day on days 4 and day 5. Data analysis used the fisher test and eta correlation test. Results: demographic characteristics of the study subjects were an average age of 51 years, high school education level, housewife occupation. As many as 46.7% were primary brain tumors and 53.3% were metastatic brain tumors with the most metastases originating from the lungs (56.3%). There was no difference in the proportion of age groups for the incidence of GIDM (p> 0.05). There was no significant relationship between age and the incidence of GIDM (p> 0.05). Conclusion: there is no difference in the proportion of the age group to the incidence of GIDM and there is no significant association between age and the incidence of GIDM.